1994
DOI: 10.1111/j.1365-2125.1994.tb04233.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender and sex steroid hormones on the plasma binding of propranolol enantiomers.

Abstract: 1 Plasma binding of tritium-labelled racemic propranolol (P) was measured by equilibrium dialysis. The unbound enantiomers were separated by h.p.l.c after chiral derivatization. The binding of (-)-P was higher than that of (+)-P. 2 Contrary to previous suggestions, a sex difference in the plasma binding of the P enantiomers (9 young women, 12 young men) was not observed. The unbound percentage of (-)-P was 9.2 ± 1.8 (mean ± s.d.) in women vs 9.1 ± 1.7 in men; for (+)-P it was 10.8 ± 1.8 vs 10.8 ± 2.1. 3 In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…However, a study examining the effect of supra-physiological levels of oestrogen on the protein binding of bupivacaine in women undergoing in vitro fertilisation procedures found that oestrogen decreased the concentrations of serum albumin and alpha 1 -acid glycoprotein, resulting in higher concentrations of free bupivacaine 82 . A similar effect was observed with exogenous oestradiol lowering levels of alpha 1 -acid glycoprotein when propranolol was studied 83 . During pregnancy the concentration of several plasma proteins decrease, resulting in an increased free fraction of drugs with high protein binding, for example lignocaine, diazepam and propranolol 84 .…”
Section: Protein Bindingsupporting
confidence: 67%
“…However, a study examining the effect of supra-physiological levels of oestrogen on the protein binding of bupivacaine in women undergoing in vitro fertilisation procedures found that oestrogen decreased the concentrations of serum albumin and alpha 1 -acid glycoprotein, resulting in higher concentrations of free bupivacaine 82 . A similar effect was observed with exogenous oestradiol lowering levels of alpha 1 -acid glycoprotein when propranolol was studied 83 . During pregnancy the concentration of several plasma proteins decrease, resulting in an increased free fraction of drugs with high protein binding, for example lignocaine, diazepam and propranolol 84 .…”
Section: Protein Bindingsupporting
confidence: 67%
“…More recent literature also suggests that extrinsic factors such as dosing regimen and formulation may impart gender related differences (39). Although we did not observe significant gender difference in the bioavailability of our parent drug (ranitidine) when administered on its own (in the absence of PEG 400) (15) many drugs including verapamil, beta-blockers such as labetalol, metoprolol and selective serotonin reuptake inhibitors have been shown to exhibit gender differences either in their metabolism or bioavailability (26,(43)(44)(45)(46)(47).…”
Section: Male Volunteersmentioning
confidence: 51%
“…Albumin concentrations do not consistently vary by sex, but AAG levels and AAG-glycosylation states vary in association with endogenous and exogenous estrogens (Brinkman- Van der Linden et al, 1996;Succari et al, 1990;Walle et al, 1994), which both decrease levels of AAG in the plasma and induce hepatic glycosylation of these proteins (Brinkman- Van der Linden et al, 1996). In addition, exogenous estrogens increase the levels of the serum-binding globulins, which include sex hormone-binding globulins, corticosteroid-binding globulin, and thyroxinebinding globulin (Wiegratz et al, 2003).…”
Section: Sex-gender Related Differences In the Cardiovascular System mentioning
confidence: 97%